2007
DOI: 10.20452/pamw.200
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of COPD and tobacco smoking in Malopolska region – results from the BOLD Study in Poland

Abstract: Introduction. There is a paucity of population-based data on chronic obstructive pulmonary disease (COPD) prevalence in Poland. To address this problem we participated in the Burden of Obstructive Lung Disease (BOLD) Initiative which was developed to provide standardized methods for estimating the prevalence of COPD and its risk factors. Objectives. The study aimed to assess the prevalence of COPD and some of its risk factors in adults aged 40 years and older in the Malopolska region in southern Poland. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
2
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 21 publications
7
40
2
6
Order By: Relevance
“…www.pneumonologia.viamedica.pl Both studies showed that men more often suffer from COPD (in the present paper -66.02%, in the KOMPAS study [11] -69.3%), which is in accordance with the results of epidemiological studies conducted on the general population, which also showed higher morbidity rates among men in Poland [4,12].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…www.pneumonologia.viamedica.pl Both studies showed that men more often suffer from COPD (in the present paper -66.02%, in the KOMPAS study [11] -69.3%), which is in accordance with the results of epidemiological studies conducted on the general population, which also showed higher morbidity rates among men in Poland [4,12].…”
Section: Discussionsupporting
confidence: 90%
“…It is estimated that currently there are 1.1 billion smokers in the world. Available data concerning the situation in Poland come from the study conducted by Professor Niżankowska-Mogilnicka and her team [4] in 2005 in the Małopolska region. The study was a part of the international BOLD study into the epidemiology of COPD.…”
Section: Wwwpneumonologiaviamedicaplmentioning
confidence: 99%
“…[6]. Tylko w jednym badaniu częstość choroby była znacznie wyższa -26% [7]. Choroba występuje częściej u mężczyzn niż u kobiet, stosunek płci wynosi 2:1 [8].…”
Section: Epidemiologiaunclassified
“…COPD is one of the most widespread chronic respiratory diseases. In Poland and in Europe, clinically important COPD is present in at least 10% of population aged ≥ 40 [4,5]. Worldwide, COPD is currently the fifth cause of the loss of DALYs (disability adjusted life years), causing large burden for healthcare budget as it is responsible for approximately 50% of total healthcare expenditures for lung diseases [6,7].…”
Section: Introductionmentioning
confidence: 99%